PENGEMBANGAN PUPUK BIOLOGIS TRICHODERMA DAN BOKASHI SEBAGAI PUPUK RAMAH LINGKUNGAN - Betty Kadir Lahati; Fatmawati Kaddas; Mila Fatmawati; Helda Sabban; Haris Mahmud (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTThis activity is part of the Entrepreneurship PKM Team program, which focuses on the development of Trichoderma-based biological fertilizers as an innovative approach to support sustainable and environmentally friendly agriculture. The main objective of this initiative is to produce and promote a biofertilizer formulated from a simple combination of Trichoderma and bokashi by the Entrepreneurship PKM Team and participating students. Through training in biofertilizer production and entrepreneurship mentoring, the program encourages active student involvement in building business units based on ecological agricultural technology. The implementation methods include technical training, fermentation practices, and strategies for product packaging and promotion. The results of the program indicate that the combination of Trichoderma and bokashi has potential to improve the growth of horticultural crops and can be further developed as a campus-based agribusiness product. Keywords: Trichoderma, biofertilizer, student, entrepreneurship, sustainable agricultureABSTRAKKegiatan ini merupakan bagian dari program Tim PKM Kewirausahaan yang berfokus pada pengembangan pupuk biologis berbasis Trichoderma sebagai inovasi pendukung pertanian berkelanjutan dan ramah lingkungan. Tujuan utama dari kegiatan ini adalah memproduksi dan mempromosikan pupuk hayati berbasis kombinasi Trichoderma dan bokashi yang diformulasikan secara sederhana oleh tim PKM Kewirausahaan dan mahasiswa. Melalui pelatihan produksi pupuk hayati dan pendampingan kewirausahaan, kegiatan ini mendorong keterlibatan aktif mahasiswa dalam membangun unit usaha berbasis teknologi pertanian ekologis. Metode pelaksanaan meliputi pelatihan teknis, praktik fermentasi, dan strategi pengemasan serta promosi produk. Hasil kegiatan menunjukkan bahwa kombinasi Trichoderma dan bokashi memiliki potensi dalam memperbaiki pertumbuhan tanaman hortikultura dan dapat dikembangkan lebih lanjut sebagai produk kewirausahaan pertanian di lingkungan kampus.Kata Kunci: Trichoderma, pupuk hayati, kewirausahaan, mahasiswa, pertanian berkelanjutan